PIRANTI FOKUS DALAM KALIMAT BAHASA INDONESIA - HS, Sunaryo (Universitas Muhammadiyah Surakarta, 2008)
The existence of focus in a sentence can be recognized from the available mark- ers used. Elements of sentence being focussed get âspecific attentionâ within an utterance. The specific elements âare separatdâ from the others by means of cer- tain strategies and markers. The strategies and markers include, among others: (1) the order, such as preposing the focussed elements; (2) the use of focussed mark- ers, such as the addition of pewatas (definite), relator yang, clitics ânya, conjunc- tion bahwa, and the word juga; and (3) the construction of specific focus, con- structions which intrinsically posite the distribution of focus by making constrast and repetition.Â Key words: fokus, piranti, pengedepanan, dan penambahan.